Effect and mediating variables of a randomized-controlled trial to promote physical activity and reduce sedentary behavior on the health-related quality of life of schoolchildren in Florianopolis, Brazil - Bandeira, Alexsandra da Silva (2022)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Desportos, Programa de Pós-Graduação em Educação Física, Florianópolis, 2022.